Genotype by environment interactions and agronomic performance of doubled haploids testcross maize (Zea mays L.) hybrids - Sserumaga, Julius Pyton; Oikeh, Sylvester O.; Mugo, Stephen; Asea, Godfrey; Otim, Michael; Beyene, Yoseph; Abalo, Grace; Kikafunda, Joseph (Euphytica, 2016)
In vivo production of maternal haploid plants and advancement in chromosome doubling technology has led to rapid production of doubled haploid homozygous lines. These in turn have boosted rapid advancement in most breeding programs. This has resulted in production of a large number of maize hybrids which need testing across production environments to select the most suitable hybrids for release and cultivation. The objective of this study was to assess the genotype 9 environment interactions (GE) for grain yield and other agronomic traits and evaluate the performance of 44 recently developed doubled haploids (DH) testcross hybrids along with six checks across five locations in Uganda. Significant mean squares for environment (E), genotype (G) and GE were observed for all studied traits. Environment explained 46.5 % of the total variance, while G and GE contributed 13.2 and 7.2 %, respectively. Genetic correlations among locations were high (0.999), suggesting little GE among environments. The 10 best testcross hybrids had a 49.2 %average grain yield advantage over the six checks at all locations. DH hybrids CKHDHH0887, CKDHH0878, CKDHH 0859, WM1210, CKDHH0858, and WM1214 were the most stable, across locations. The DH testcross hybrids produced higher grain yield and possessed acceptable agronomic traits compared to the commercial hybrids developed earlier. Use of the best DH testcross hybrids, well targeted to the production environments, could boost maize production among farmers.
Keywords: Doubled haploids; East Africa; 9 environment Grain yield Maize Stability; Genotype 9 environment; Grain yield; Maize; Stability